1993
DOI: 10.1002/stem.5530110920
|View full text |Cite
|
Sign up to set email alerts
|

The role of stem cell factor in mobilization of peripheral blood progenitor cells: Synergy with G‐CSF

Abstract: Abstract. The use of cytokine mobilized peripheral blood progenitor cells (PBPC) in transplantation following chemotherapy has led to enhanced engraftment. Granulocyte-colony stimulating factor (G-CSF) has been shown in a number of clinical studies to be an effective mobilizer of PBPC. preclinical data in mice and primates have demonstrated a potential role for the use of stem cell factor (SCF) in mobilization of PBPC. In the studies presented here, low doses of SCF are shown to synergize with optimal doses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…In the present paper, based on the study of a homogeneous group of 22 breast cancer patients, we have confirmed previous observations 16 indicating that a high number of CD34 ϩ PB HPC can be obtained with a mobilization protocol based on SCF plus G-CSF and cyclophosphamide. The median number of total CD34 ϩ HPC harvested in one leukapheresis session was 13 Ϯ 13 ϫ 10 6 CD34 ϩ cells/kg body weight and therefore much higher than reported for cyclophosphamide plus G-CSF in the absence of SCF.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present paper, based on the study of a homogeneous group of 22 breast cancer patients, we have confirmed previous observations 16 indicating that a high number of CD34 ϩ PB HPC can be obtained with a mobilization protocol based on SCF plus G-CSF and cyclophosphamide. The median number of total CD34 ϩ HPC harvested in one leukapheresis session was 13 Ϯ 13 ϫ 10 6 CD34 ϩ cells/kg body weight and therefore much higher than reported for cyclophosphamide plus G-CSF in the absence of SCF.…”
Section: Discussionsupporting
confidence: 90%
“…14,15 Previous studies have shown that once administered in combination with other cytokines such as G-CSF, SCF has a synergistic effect on enhancing mobilization of CD34 ϩ HPCs into the PB. 16 Accordingly, accumulating evidence exists that the combined use of G-CSF and SCF is associated with higher mobilization rates as compared to G-CSF alone. [17][18][19] Moreover, SCF has become an alternative agent in patients who show a poor response to other mobilization protocols.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26] Cytotoxic agents, with or without growth factor, are known to damage both hematopoietic and mesenchymal marrow stem cell compartments, thus suggesting that different chemotherapy agents might affect not only the quantity, but also the quality of mobilized progenitors. [27][28][29][30] No definitive assessment exists concerning the best chemotherapy mobilizing regimen given with G-CSF. 31,32 Hematological parameters including MNC or CD34 + cell pre-apheresis counts can probably predict hematopoietic stem cell collection.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21] Whether G-CSF alone can stimulate a true in vivo expansion, or an increase in the total number of progenitor cells or their precursors, or whether it acts only to redistribute progenitors within the hematopoietic tissues remains controversial. [22][23][24] Although G-CSF can act synergistically with IL-3 to induce proliferation of dormant murine stem cells, its contribution to initiating expansion of dormant human stem cells when utilized in solo has never been demonstrated.…”
Section: G-csf Stem/progenitor Cell Mobilizationmentioning
confidence: 99%